2018
DOI: 10.1021/acs.analchem.8b02301
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Long-Term Imaging of Cellular RNA by Fluorescent Carbon Dots with Surface Isoquinoline Moieties and Amines

Abstract: Cellular RNA dynamics are closely associated with a vast range of physiological processes that are mostly long-lasting. To uncover the association between RNA dynamics and these processes, fluorescent RNA probes with high specificity, photostability, and biocompatibility are compulsory. Herein, a series of fluorescent carbon dots (CDs) have been prepared by one-pot hydrothermal treatment of o-, m-, or p-phenylenediamines with triethylenetetramine. Only CDs derived from the meta precursor ( m-CDs) with excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…The main function of RNA is to realize the expression of genetic information on proteins and to bridge the process of transforming genetic information to phenotype. Huang and co‐workers successfully developed a series of CDs by a hydrothermal method using triethylenetetramine and o ‐, m ‐, or p ‐phenylenediamine . The in vitro experiments revealed that the m ‐CD could specifically bind cellular RNA and monitor RNA dynamics during apoptosis, mitosis, and proliferation in real time (Figure b).…”
Section: Cds For Bioimaging and Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main function of RNA is to realize the expression of genetic information on proteins and to bridge the process of transforming genetic information to phenotype. Huang and co‐workers successfully developed a series of CDs by a hydrothermal method using triethylenetetramine and o ‐, m ‐, or p ‐phenylenediamine . The in vitro experiments revealed that the m ‐CD could specifically bind cellular RNA and monitor RNA dynamics during apoptosis, mitosis, and proliferation in real time (Figure b).…”
Section: Cds For Bioimaging and Diagnosticsmentioning
confidence: 99%
“…b) Illustration of specifically bind to cellular RNA for long‐term monitoring of RNA dynamics during cell apoptosis, mitosis, and proliferation. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Cds For Bioimaging and Diagnosticsmentioning
confidence: 99%
“…They usually have carbonaceous graphitic core of <10 nm with varying degrees of oxidation (Shi, Li, & Ma, ). These fluorescent carbon nanoparticles can be synthesized from various carbon precursors such as citric acid (He et al, ; Khan, Verma, Chethana, & Nandi, ; Lan et al, ; Liu, Tian, Tian, Wang, & Yang, ; Shangguan et al, ; Shi et al, ; Shu et al, ; Wu, Li, Ling, Huang, & Jia, ; Yang et al, ; Zhang et al, ), activated carbon powder (Chai et al, ), hyaluronic acid (Zhang et al, ), phenylene diamine derivative (Cheng et al, ; Hua, Bao, & Wu, ; Liu, Y., Duan, W., et al, 2017; Song, W., Duan, W., et al, 2017; Xia, Chen, Zou, Yu, & Wang, ), flour (Zhang et al, ), 2‐azidoimidazole (Tang, Lin, Li, & Hu, ), thiomalic acid (Safavi, Ahmadi, Mohammadpour, & Zhou, ), aminosalicylic acid (Song, Y., Zhu, C., et al, 2017), sodium alginate‐tryptophan (Zhu et al, ), neutral red‐triethyl amine (Jiao et al, ), capsicum (Chen et al, ), ethanol (Gao, Ding, Zhu, & Tian, ; Qu, Zhu, Shao, Shi, & Tian, ; Zhu, Qu, Shao, Kong, & Tian, ), (3‐aminopropyl) triethoxysilane (Zou et al, ), malic acid (Zhi et al, ), folic acid (Liu et al, ), and so on. Furthermore, various cost‐effective and simple procedures have been established for their preparation that include solvothermal treatment (Chen et al, ; Zhu et al, ), thermal degradation (Shi et al, ), high temperature reflux (Lan et al, ), microwave‐assisted synthesis (He et al, ; Tang et al, ), pyrolysis (Zhang et al, , ), and oxidative acid treatment (Safavi et al, ).…”
Section: Different Types Of Fluorescent Carbon Nanomaterialsmentioning
confidence: 99%
“…Furthermore, various cost‐effective and simple procedures have been established for their preparation that include solvothermal treatment (Chen et al, ; Zhu et al, ), thermal degradation (Shi et al, ), high temperature reflux (Lan et al, ), microwave‐assisted synthesis (He et al, ; Tang et al, ), pyrolysis (Zhang et al, , ), and oxidative acid treatment (Safavi et al, ). Following these approaches, fluorescent carbon nanoparticles are synthesized with wide range of emission from ultraviolet to visible to near‐infrared (Cheng et al, ; Jiao et al, ; Lan et al, ). In particular, the fluorescence property of these carbon nanoparticles has been tuned by varying chemical composition, particle size, and introducing surface defects.…”
Section: Different Types Of Fluorescent Carbon Nanomaterialsmentioning
confidence: 99%
“…[24,25] Moreover,t here are also reports [22,26] of regulating the emission wavelength by controlling the particle size [5,27] of PDs. Secondly, the FSG play ac rucial role in customizing the application-targeted PDs.S everals tudies have attempted to design PDsw ith specific FSG for targeting, [28,29] probing, [30,31] catalyzing, [32] and other applications. [33] For example, Xu'sg roup [34] developed l-PDs and d-PDs with chiral FSG from l-o rd-cysteine, respectively,a t6 08C.…”
Section: Introductionmentioning
confidence: 99%